Strategi Personal Selling Produk Jasa IT - Bambang Dwi Cahyo; Elva Meiliza (Marcommers : Jurnal Marketing Communication and Advertising, 2008)
Tile deuelopment ofJ, !formation technology growing at this timemokingPT. MastersgstemJi!fotomatocreoteotrointng center company, namely PI'./!. ctiuindofr!formationsgstem that has riprodi!ctfonn offTframing services. The product of PI' Actiuindo is training services of a computersqjtoore, To make easier in selling its IT training is necessary personal selling strategy. Therefore, the importance of personalselling OS a keg element in the direct marketing communications, researchers chose to make the research personalse!ting strategy on PT. Actiuindolr!formationsgstem. Thepurposeqfthisresearchisto determine how the strategy qfpersonolselling of PI'. Acti'urndo flat'ormotion System. This research using method desertj, tiue quantattue with case stud!!. Tile results obtained are the implementction of personal selling strategy on PTActiuindo System 17!formatics. Start from salting personal data intering steps, soles coils, prospect, closing andseruicestoconsumers, The typeqfpesonol selling strategies used PT. f^formation System is professional, beside that also using a type of salesperson soles strategy to buglersandsellers to group buyers.